Treatment of benign positional paroxysmal vertigo in clinical settings in India: a cross sectional pilot survey - P., Sreeram; Prabhakaran, Prabash (International Journal of Advances in Medicine, 2022)
Background: The usage pattern and effectiveness of various treatment strategies for benign positional paroxysmal vertigo (BPPV) have not been widely reported in routine clinical settings in India. The aim of the study was to understand treatment patterns and level of symptom improvement in Indian patients presenting with symptoms of BPPV in clinical practice. Methods: A cross-sectional pan-India survey was conducted with leading neurologists and otolaryngologists. A detailed questionnaire was shared with specialists which was followed by semi-structured telephonic interviews to gather a deeper understanding of their treatment practices. The obtained data was analyzed using appropriate statistical methods. Results: A total of 5 neurologists and 8 ENT specialists completed the survey. Physicians reported that age, but not gender, was an important factor when selecting appropriate treatment. Specialists reported that in their clinical practice symptom improvement is better with betahistine plus maneuvers compared to betahistine only alone (97% verses 90% cure rate) and is comparable with maneuvers (97% verses 98% cure rate, respectively). Dix Hallpike and supine roll test using videonystagmography were the most recommended tests used to diagnose BPPV. Betahistine plus maneuvers was the most commonly prescribed treatment for BPPV, and clinicians observed greater decrease in the severity of BPPV symptoms with betahistine plus maneuvers versus betahistine alone or maneuvers. The Visual analog scale (VAS) was the most widely used scale for assessing severity of BPPV symptoms. Conclusions: These findings indicate that betahistine plus maneuvers provides better control over symptom severity in patients with BPPV.